Os efeitos da abertura comercial sobre o desemprego no Brasil no período de 1981-2004 - Costa, Jaqueline Severino da (2007)
The aim of this work is to analyze the evolution of the unemployment in Brazil in the period of 1981-2004, trying to verify the effects of the trade openness with special attention to the individual qualification. To establish the connections of the variable effect on the unemployment logit was used, that is a model based on variable of dicotomics or qualitative replies. The evidences show that to Brazil, as well as to a large extent of the developed countries and in developments, the trade openness is important in way that it has facilitated the entrance of Skill-Biases Technological Change (SBTC). In this direction it has an increase of demand skill labour, opposing the prediction of the model trade Heckscher-Ohlin-Samuelson (H-O-S). To this model the developed countries would export goods that are intensive in skill labour and the developing countries would export goods that are intensive in unskill labour. The great discussion is which thesis is better adjusted to the Brazilian reality to explain unemployment rate, trade openness or Skill-Biases Technological Change. The new technologies are work savers and what an increase in the levels of unemployment among unskill labour is observed. As the new technologies demand more qualified man power an increase of offers of this is verified, therefore is possible to infer that the education became an important variable to determine unemployment. At last, the results allows to show that the process of trade openness with technological changes seems to be the best justification to explain unemployment in Brazil, besides considering the low level of economic activity in the period and low skill of the individuals.